Benchmarking atomically defined AFM tips for chemical-selective imaging. Issue 32 (4th August 2021) - Schulze Lammers, Bertram; Yesilpinar, Damla; Timmer, Alexander; Hu, Zhixin; Ji, Wei; Amirjalayer, Saeed; Fuchs, Harald; Mönig, Harry
Abstract : Challenge of four common AFM tip-terminations: The high rigidity and moderate chemical passivation of CuOx-tips provide site-selective contrast on a metal–oxide. Abstract : Controlling the identity of the tip-terminating atom or molecule in low-temperature atomic force microscopy has led to ground breaking progress in surface chemistry and nanotechnology. Lacking a comparative tip-performance assessment, a profound standardization in such experiments is highly desirable. Here we directly compare the imaging and force-spectroscopy capabilities of four atomically defined tips, namely Cu-, Xe-, CO-, and O-terminated Cu-tips (CuOx-tips). Using a nanostructured copper-oxide surface as benchmark system, we found that Cu-tips react with surface oxygen, while chemically inert Xe- and CO-tips allow entering the repulsive force regime enabling increased resolution. However, their high flexibility leads to imaging artifacts and their strong passivation suppresses the chemical contrast. The higher rigidity and selectively increased chemical reactivity of CuOx-tips prevent tip-bending artifacts and generate a distinct chemical contrast. This result is particularly promising in view of future studies on other metal–oxide surfaces.